Video classes for adolescent nursing consultations: development and validation - Franciéli Hollas Rosalem; Edlamar Kátia Adamy; Rafael Gué Martini; Teresa Martins; Elisangela Argenta Zanatta (Revista Gaúcha de Enfermagem)
ABSTRACT Objective: Create and validate the content of video lessons to support nurses when carrying out adolescent consultations in Primary Health Care. Method: Methodological research carried out in four stages: 1) Exploration, with 83 nurses and two literature narrative reviews; 2) Construction of scripts and storyboards; 3) scripts and storyboards’ content validation; 4) Video classes production. Data analysis was conducted using the Content Validity Index. Results: The exploratory stage revealed that 85.5% of nurses carry out consultations with adolescents and 44.6% face difficulties. The most cited topics of interest were legal aspects of care, adolescent consultation, pregnancy and risk assessment in adolescence. In the review carried out with the objective of identifying a script for producing the video lessons, no one was found that met the needs of the study. The other narrative reviews showed that nursing training for adolescent consultations is incipient. 14 expert nurses validated the content with a Content Validity Index above 0.9. Afterwards, a series of four video lessons entitled “Teen talk” was produced. Conclusion: content was validated in terms of objective, structure/presentation and relevance, allowing the video classes to assist in the professional qualification of nurses to carry out consultations for adolescents.